Femininitie: a detail - Marques Massara, Izabel Haddad (2013)
The present text intends to approach the question of femininity in relation to the theme of clothing. Freud concluded that “braiding and weaving” was meant to cover the phallic lack, and Lacan reminded us with his text of the behavior of women as authentic weavers in the rearrangements of the drives that they have set up in their animic lives. We depart from some authors of the literature to demonstrate that the Freudian and Lacanian thesis only corroborate the hypothesis that there is an intricate relationship between women and clothing, that is, between femininity and “the function of the veil”. However, the feminine employs the veil-which is the clothes, according to psychoanalysis- to cover a women’s supposed lack. In this sense, the clothing is a phallic exit that would hide castration. The text points to another possibility of apprehension of the feminine through the theme of the detail, since the qualities of this little and subtle object present an exit through each woman’s feminine and unique style. That is, if clothing presents an exit through the phallus, the detail marks the whole with a cut that reopens the issue of the woman with her own lack.